Retardasi Mental Sedang pada Anak Perempuan Usia 9 Tahun: Sebuah Laporan Kasus - Indah Anita Dewi; Cahyaningsih Fibri (CV. Jasa Sukses Abadi, 2022)
Mental retardation is a state of incomplete or cessation of mental development that affects a person's level of intelligence. This is marked by impaired skills during the developmental period that affect cognitive, language, motor and social abilities. Mental retardation is caused by several factors such as genetic, environmental and psychosocial factors. Mental retardation is classified as mild, moderate, severe and very severe. The incidence of mental retardation is difficult to know accurately because it is generally only detected at an older age. However, it is estimated that 10-15 per 1000 children in developing countries are mentally retarded with 1.5 times more males than females. This case report discusses moderate mental retardation in a 9-year-old girl who came with complaints of difficulty following lessons at school since 2 years ago. The patient's parents said that the complaints were getting worse because of the increasing level of difficulty in learning and the online learning process at school. The therapy given is in the form of psychotherapy and psychoeducation to patients and families who care for patients.